Adolescents' risky sexual behaviour and efficacy of Psycho-education intervention programme among Secondary school students in Oyo State (2004)
The study examined adolescents' attitude to risky sexual behaviour and the efficacy of psycho-education intervention programme among 150 Secondary School Students; 100 students were used for the experimental study while 50 were used as the control. Specifically it is aimed at finding out the effectiveness of the psycho-education preventive intervention programme on adolescents' altitude to sexual risk behaviour among adolescents. Four hypotheses were postulated while analysis of variance and t-test for independent samples were used to analyse the data collected. Findings indicate that adolescents who were exposed to the psycho-education preventive intervention programme scored lower in risky sexual behaviour measures than those who were not exposed to psycho-education. Students with low and high quality of life did not differ significantly in their attitude towards risky sexual behaviour. One of the implications of the findings is that irrespective of social status, the adolescents engaged in risky sexual behaviour. It is therefore recommended that preventive intervention programmes should target adolescents at the various socioeconomic levels of the society.